The labor market effects of trade union heterogeneity - Marco De Pinto; Jochen Michaelis (Philipps-University Marburg, School of Business and Economics, 2018)
Empirical evidence suggests that the bargaining power of trade unions differs across firms and sectors. Standard models of unionization ignore this pattern by assuming a uniform bargaining strength. In this paper, we incorporate union heterogeneity into a Melitz (2003) type model. Union bargaining power is assumed to be firm-specific and varies with firm productivity. This framework allows us to re-analyze the labor market effects of (i) a symmetric increase in the bargaining power of all unions and (ii) trade liberalization. We show that union heterogeneity unambiguously reduces the negative employment effects of stronger unions. Firm-specific bargaining power creates a link between unionization and the entry and exit of firms, implying a reduction of the unions' expected bargaining power. Moreover, union heterogeneity constitutes an (un)employment effect of trade liberalization. If unions are most powerful in the high-productivity (low-productivity) firms, trade liberalization will increase (decrease) unemployment.
Keywords: F1; F16; J5; 330; Trade Unions; Bargaining Power; Firm Heterogeneity; International Trade; Unemployment